Antibody-independent activation of the alternative complement pathway by measles virus-infected cells. - Sissons, J G (1980)
When HeLa cells acutely infected with measles virus were incubated in a mixture containing only the six proteins of the alternative pathway of complement activation (C3, factors B and D, beta 1H, C3b inactivator, and native properdin) without antibody, there was activation of the alternative pathway as shown by progressive uptake of 125I-labeled C3b onto the cell surface. This C3b uptake was blocked by EDTA and was not shown by uninfected cells. The rate of 125I-labeled C3 uptake by infected cells was the same in the absence and presence of properdin; however, when antiviral IgG was bound to the cell surface, the rate of C3 uptake was increased in the presence of properdin. Significant 125I-labeled C3 uptake was first detectable when cells were studied at 12 hr after infection, when cells expressed viral polypeptides on their surface. There was also progressive uptake of 125I-labeled C3 onto measles virus-infected cells incubated in human serum depleted of both IgG and C4. Hence, the human alternative pathway of complement activation can be initiated on the surface of measles virus-infected cells independent of IgG antibody. However, lysis of the infected cells only occurs when antiviral antibody is present.